Alerting the illusion of smoking improves quality of life in Chinese male cancer survivors - Juan Xia; Peng Wu; Jiwei Wang; Jinming Yu (Cancer Medicine)
Abstract Objective To examine the association between smoking status and quality of life (QOL) among cancer survivors in China. Methods A cross‐sectional study was performed in 2725 male cancer survivors who were members of Cancer Rehabilitation Club and completed the questionnaires in 2013. Using linear regression models adjusted for confounders, we measured the association between QOL and former smokers as well as current (occasional, <10 cigarettes/day, and ≥ 10 cigarettes/day) smokers compared with never smokers. Results Current smokers were reported to have higher scores in social, role, cognitive functioning, and had lower scores in nausea/vomiting, pain, dyspnea, and insomnia (P < 0.05). Former smokers had higher global health status and experienced less appetite loss and constipation (P < 0.05). Compared with never smokers, those former smokers and current smokers had significantly high scores on the global health status, social functioning, role functioning, and cognitive functioning (P < 0.05). And they had lower scores in some aspects of symptom scale (P < 0.05). Considering the dose of smoking, the scores were increased in functional subscales and decreased in symptom subscales with the increase of tobacco use, though few variables had statistical significance. As for smoking cessation, the proportion of lung cancer survivors who quit smoking was higher than that of other types of cancer survivors. Conclusion Our study suggested the possibility that in China, where smoking prevalence is still high, continued smoking was associated with high QOL scores. The phenomenon may be obscured by some potential reasons, including subjectivity of questionnaire, special substances of cigarettes, Chinese unique culture of tobacco use, and much more. The results reminded researchers and clinicians some underlying situations among smokers in China and prompted a strong call for the implementation of a comprehensive tobacco‐control policy and specific public health educational strategies among not only lung cancer survivors but other types of cancers survivors.